2001
DOI: 10.1021/bi015677t
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of α-Tubulin Tail Peptide:  Implications for Tail−Body Interaction

Abstract: The carboxy-terminal segments of the alpha/beta-tubulins are flexible regions rich in acidic amino acid residues. It is generally believed that these regions play crucial roles in tubulin polymerization and interaction with many ligands, including colchicine. Exactly how these effects are exerted are not known at present. One such interesting aspect is the pH dependence of colchicine-tubulin interaction and the influence of the alpha-tail on the binding interaction. We have investigated the location of the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…5 f ). Moreover, solution NMR and molecular dynamics studies show that the α-tail is not fully extended, but adopts a slightly helical conformation with a ~29 Å 45 span. Thus, in the absence of large conformational changes upon binding, it is likely that TTL recognizes α-tubulin on the surface that would form the longitudinal interface in the context of the MT.…”
Section: Resultsmentioning
confidence: 99%
“…5 f ). Moreover, solution NMR and molecular dynamics studies show that the α-tail is not fully extended, but adopts a slightly helical conformation with a ~29 Å 45 span. Thus, in the absence of large conformational changes upon binding, it is likely that TTL recognizes α-tubulin on the surface that would form the longitudinal interface in the context of the MT.…”
Section: Resultsmentioning
confidence: 99%
“…75 Though colchicine binds at the alphabeta interface of tubulin far from its carboxy terminal end, several properties of colchicines-tubulin interactions such as pH-sensitivity, off-rate, on-rate, and the stability of the colchicines-binding site are greatly influenced by the a C-terminal of tubulin as discussed in the previous section. 67 Earlier Pal et al 76 suggested the presence of ''tail-body interaction'' between the negatively charged a-Cterminus of tubulin with the positively charged residues of the main body of tubulin. Vertebrate tubulin contains four b-tubulin classes designated as b I , b II , b III , and b IV in relative amounts of 3, 58, 25, and 13% respectively.…”
Section: S T R U C T U R a L B A S I S O F T H E D I F F E R E N T mentioning
confidence: 99%
“…For the unphosphorylated 1-39 domain, the ratio is ϳ1:7.5 (for prolate as well as oblate ellipsoids) indicating a nonspherical shape. In contrast, a completely unstructured 13-residue peptide gave an axial ratio value of ϳ1:20 by the same technique (31). A much longer peptide chain, such as p53 transactivation domain, if completely disordered, should give even higher axial ratios.…”
mentioning
confidence: 94%